THE NATURE OF LEADERSHIP, ITS UNIQUE RESPONSIBILITIES, AND CONFLICT RESOLUTION SKILLS - Alijonov Nurbek Ulugbek ogli (Bright Mind Publishing, 2025)
The article explores the demands and responsibilities placed on managerial staff, the nature of conflicts within teams and approaches to their prevention and resolution through destructive methods, along with the essence and typology of management styles.
Keywords: Leader, Personality, Management, Liberal, Authoritarian, Democratic, Destructive, Responsibility.